PENERAPAN SISTEM PERKANDANGAN PADA USAHATERNAK BABI DI WAYARI, NEGERI SULI, KECAMATAN SALAHUTU, KABUPATEN MALUKU TENGAH - Joseph, Godlief (Universitas Pattimura, 2023)
Pigs are animals that have long been kept and developed for the purpose of meeting umanity's need for meat. Pig farming businesses in the community, especially in Wayari, Negeri Suli, Salahutu District, Central Maluku Regency, are still traditional. Pigs that are kept generally do not have good cage equipment and the feed they are given is only food scraps and agricultural waste. The aim of this service is to increase the knowledge and skills of pig farmers. Meanwhile, the benefit to be achieved is that farmers can run their business well, especially with a feeding system and housing system as well as cage equipment that meets the requirements. Breeders have a positive response because this is something that is good for them. Farmers have also realized that when feeding pigs it is necessary to provide additional feed in the form of bran so that it can increase the nutritional value of the rations given. Farmers have also been able to make guard rails so that they can reduce the death rate of pre-weaning piglets due to being crushed by their mothers. It is recommended that ongoing assistance is needed in the form of training in making separation cages, cage mats and heaters for newborn piglets to reduce the death of pre-weaning piglets.